THE KNOWLEDGE OF CORPORALITY IN THE PROFESSIONAL FORMATION IN PHYSICAL EDUCATION (Fiep Bulletin - online, 2015)
We propose in this article a dialog about the abilities which can be developed through the human body, what means, in a way of life full of significances, where the body will also be an important part for the comprehension about what should be learned, and its influence in forming students of Physical Education. “Who will educate the educators?” This topic, brought out by Karl Marx in one of his thesis about Feuerbach, quoted by Morin (1999), which understands that “Will be a minority of educators, stimulated by the faith in the need to change the thought and regenerates the education”, fortifies the preoccupation we have by proposing this study. Notice that these two assertions only make real in a education which embraces the whole body, by contemplating action and feeling, the thinking and the acting. But how to develop this possibility in a formation which still appreciates inactivity as a privileged way to the development of apprenticeships? Here we present a reflection, advocating that paradigmatic changes will only become possible with a chance of focus about corporality, in a sense that it can't educate a citizen neglecting essential attitudes to his formation, as those ones which generates conscious movement, happiness, curiosity, cooperation, affectivity, responsibility and ethics, motivating, only and mainly, the competition and the individualism, because, as society appreciates thinking more than acting, putting aside the totality which overlays the human being, the body is, more and more, putted aside and reinforced as a compartmentalized biological conjoint, contributing a lot to misperceiving it.
Keywords: corporality; formation; Physical Education